Labour market outcomes after vocational training in Germany : Equal opportunities for migrants and natives? - Burkert, Carola [Verfasser]; Seibert, Holger [Verfasser] (My University, 2007)
"German in-firm vocational training combines training on the job and learning in vocational schools. The so called 'dual system' absorbs roughly two thirds of German school leavers every year. After between two and four years of standardized training, it provides them with a generally accepted qualification in a wide range of occupations. Using Spence's Signaling Theory, hypotheses are derived concerning different labour market outcomes of foreigners who successfully completed an in-firm vocational training course and their German counterparts. The integration potential of the dual system is tested empirically according to its risk factors unemployment, occupational mismatch and skill mismatch using longitudinal registration data (1977-2004). Different nationalities are compared with Germans with respect to their first employment after leaving the dual system. Today, most of the young migrants who go through the dual system are as successful on the labour market as Germans. In-firm vocational training apparently provides migrant youth with the skills and techniques necessary for a successful transition to the labour market. However, they have restricted transition chances due to having higher unemployment rates, occupational mismatch and skill mismatch. But even if we control for relevant variables that determine transition chances, restrictions at labour market entry still remain for individual nationalities: compared to Germans, migrant men and especially migrant women have a higher risk of unemployment and occupational mismatch." (Autorenreferat, BIBB-Doku)
Keywords: P 1.1 Jugendliche; P 1.5 Migranten; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; G 1.3.2.2.3 Zweite Schwelle, in Arbeit; Betriebliche Berufsausbildung; Ausländischer Jugendlicher; Bildungsbeteiligung; Ausbildungserfolg; Einflussfaktor; Berufseinmündung; Zweite Schwelle; Arbeitsmarktchance